Electron bridging structure glued yolk-shell hierarchical porous carbon/sulfur composite for high performance Li-S batteries. (1st December 2018) - Wu, Feng; Zhao, Shuangyi; Chen, Lai; Lu, Yun; Su, Yuefeng; Li, Jian; Bao, Liying; Yao, Jinyu; Zhou, Yiwei; Chen, Renjie
Abstract: Despite various carbon materials have been extensively applied in lithium-sulfur (Li-S) battery, efficient optimization of the material structure for further performance improvement is remaining a great challenge. Herein, we fabricated electron bridging structure glued yolk-shell hierarchical porous carbon (HPC) nanospheres containing a microporous shell and a mesoporous core as cathode host for Li-S battery. In which, the inner mesoporous core acts as a sulfur reservoir to entrap polysulfide species, and the outer micropores shell provides not only large contact area between sulfur and conductive substrate, but also physical confinement and chemical adsorption to trap polysulfide. This yolk-shell HPC was further glued by an electron bridging structure consisting of carbon nanotube (CNT) decorated polyaniline (PANi), who can further suppress the shuttle effect benefit from PANi and afford a highly conductive network by affording a "point-to-plane" type electron transport mode instead of the "point-to-point". As a result, this designed cathode material exhibits a high initial specific capacity of 1372 mAh g −1 at 0.2 A g −1, and excellent cycling stability with a capacity decay of 0.083% per cycle over 500 cycles at 2 A g −1 . This strategy provides a promising approach for the design of multifunctional carbon materials for high performance Li-S batteries. Highlights: The yolk-shell HPC can simultaneously accumulate plenty sulfur and limit polysulfide shuttles. The electron bridging structure provides a conductive network by affording a point-to-plane type electron transport mode instead of the point-to-point. The combine of the hierarchical core-shell architecture and electron bridging structure is realized. The cathode possesses high sulfur loading, high electrical conductivity and the ability to limit polysulfide shuttles at the same time.